2010
DOI: 10.1161/hypertensionaha.110.152058
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cell Differentiation to an Osteogenic Phenotype Involves TRPM7 Modulation by Magnesium

Abstract: Abstract-Arterial calcification, common in vascular diseases, involves vascular smooth muscle cell (VSMC) transformation to an osteoblast phenotype. Clinical studies suggest that magnesium may prevent this, but mechanisms are unclear. We assessed whether increasing magnesium levels reduce VSMC calcification and differentiation and questioned the role of the Mg 2ϩ transporter, transient receptor potential melastatin (TRPM)7 cation channels in this process. Rat VSMCs were exposed to calcification medium in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
153
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(173 citation statements)
references
References 53 publications
12
153
4
Order By: Relevance
“…Transient receptor potential melastatin 7 (TRPM7), a member of TRP melastatin subfamily, is a Ca 2+ -permeable nonselective cation channel [6][7][8] whose expression has been detected in VSMCs. 9,10 Through Ca 2+ signals, TRPM7 channels participate in many physiological and pathophysiological processes, including directed cell migration, 11 cell adhesion, 12 anoxic neuronal death, 13 and transdifferentiation of cardiac fibroblast. 14 Moreover, TRPM7 is essential for embryonic development, as evidenced by genetic ablation leading to embryonic lethality.…”
mentioning
confidence: 99%
“…Transient receptor potential melastatin 7 (TRPM7), a member of TRP melastatin subfamily, is a Ca 2+ -permeable nonselective cation channel [6][7][8] whose expression has been detected in VSMCs. 9,10 Through Ca 2+ signals, TRPM7 channels participate in many physiological and pathophysiological processes, including directed cell migration, 11 cell adhesion, 12 anoxic neuronal death, 13 and transdifferentiation of cardiac fibroblast. 14 Moreover, TRPM7 is essential for embryonic development, as evidenced by genetic ablation leading to embryonic lethality.…”
mentioning
confidence: 99%
“…Feeding mice with low vitamin D for 16 wk, Schmidt et al (89) observed more calcified spots in the aortic valve than those given adequate vitamin D, accompanied by higher expressions of BMP2 and Runx2. Similarly, in animal VSMCs calcification models, administration of Mg dose-dependently decreased expressions of BMP2, osteocalcin, and ALP, leading to amelioration of VSMCs calcification (44,70).…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 97%
“…Montes de Oca et al reported that Mg inhibited Wnt/β-catenin signaling pathway and reversed osteogenic transformation of VSMC [49]. Mg transport through the cell membrane mediated by transient receptor potential melastatin 7 (TRPM7) is important in VSMC calcification [49][50][51]. Previous studies have suggested that P uptake through phosphate transporter-1 (Pit-1) is also essential in calcification [52].…”
Section: Mg and Dialysis Therapymentioning
confidence: 99%